Analysis of the Impact of Implementing PSAK 72 on Financial Performance and Price Earning Ratio in Non-Cylical Consumer Companies Listed on the Indonesian Stock Exchange for the 2018-2021 Period - Sumardianti, Ade Tari; Enggar Diah Puspa Arum; Muhammad Gowon (Indonesian Journal of Economic & Management Sciences, 2023)
The purpose of this study is to analyze how the implementation of PSAK 72 has affected the price-earning ratio and financial performance of non-cyclical consumer firms that are listed on the Indonesian Stock Exchange for the years 2018 through 2021. Quantitative study employing secondary data is being conducted here. All non-cyclical consumer firms listed on the IDX for the period of 2018–2021 make up the population of this study. To collect 72 samples, the sampling method employed a purposive sampling methodology with many criteria. With SPSS 29.0, a straightforward linear regression data analysis method is employed. The study's findings demonstrate that while the solvency ratio (DER) and price earning ratio (PER) have a favorable and substantial impact, the application of PSAK 72 to financial performance with profitability ratios (ROA) and liquidity (CR) has no effect